Bibliography of Art and Architecture in the Islamic World: volume 1: “Art” (837 pages) and volume 2: “Architecture” (653 pages) By Susan Sinclair, ed. (Leiden: Brill, 2012.) (American Journal of Islam and Society, 2014)
Index Islamicus, begun in 1906, is a database of bibliographic information ofpublications in all areas of studies connected with the Islamic world. Since thattime, interest in Islamic art and architecture has surged from specialists to manyscholars, students, and general interest worldwide. The recent and updated supplementsBibliography of Art and Architecture in the Islamic World, edited bySusan Sinclair, who was assisted by Heather Bleaney and Pablo Garcia Suarez,fills a serious void by listing the materials from 1906 to 2011.Sinclair, an independent scholar with a Ph.D. from the University ofLondon’s Courtauld Institute of Art, is currently researching material in themedievalArab world and has served as the co-editor of the Index Islamicussince 2007. With the support of the university’s renowned School of Orientaland African Studies, she was able to comb the archives of the United Kingdom’sleading institutions, including the National Art Library in London,the British Library, the library of the Warburg Institute, the Cambridge UniversityLibrary, and the University of Oxford libraries, as well as importantcollections located in Spain (e.g., the Biblioteca Nacional de España, theBiblioteca Islámica, and the libraries of Consejo Superior de InvestigacionesCientificas). The compilation of resources from these vast collections aswell as the material available online has brought this bibliographic collectionto a new level.At first glance, the material may seem to be no more than a listing ofsources on the subject, with no “content” per se to read. However, the valueof such texts and of this set in particular is that the bibliographic listings aregrouped by type and subtypes, which enable researchers in particular areas toaccess a wealth of information not necessarily accessible by other search enginesor mechanisms ...